Investigation of some physical and mechanical properties of concrete produced with barite aggregate - Esen, Yuksel; Yilmazer, Berivan (Academic Journals, 2010)
This study analyzed some physical and mechanical properties of concrete produced with barite (BaSO4) aggregate supplied from Mus province of Turkey. Unit weight (UW), water absorption (%), ultrasound pulse velocity (UPV), Schmidt hardness (SH), modulus of elasticity (ME), compressive strength (CS), tensile strength (TS) and thermal conductivity (TC) of the concrete were analyzed. For the experiments, 6 series of concrete containing 0, 10, 20, 30, 40 and 50% volume of barite aggregate were prepared. To determine thermal conductivity coefficient, this ratio was increased to 100%. Experimental results for normal concrete and barite concrete were compared.
Keywords: Concrete; barite; heavyweight concrete; thermal conductivity